Evaluation of Soil Fertility Status in Shifting Cultivation of Upland Rice in Tanah Merah Village, Warmare District, Manokwari Regency, West Papua - Karoror, Sitti A.; Musaad, Ishak; Kubangun, Siti H. (Jurnal Biologi Papua, 2025)
This study was conducted on the agricultural land of Indigenous Papuan communities in Tanah Merah Village, Warmare District, Manokwari, where shifting cultivation is practiced in conjunction with a subsistence and semi-commercial farming system for upland rice (Oryza sativa). The research employed a descriptive method with a survey technique to determine the locations for composite soil sample collection in shifting cultivation fields planted with upland rice. The results showed that the soil in the study area has a clay texture with a yellowish-red to reddish-yellow color. The soil reaction (pH) is classified as acidic, slightly acidic, and neutral. Organic carbon content ranges from high to low. Total nitrogen content is classified as moderate in the upper soil layer and low in the lower soil layer across all land sections. Total phosphorus and available phosphorus contents are categorized as low to very low. Total potassium content is classified as moderate to low. Cation exchange capacity (CEC) and base saturation (BS) show varied values, leading to a low soil fertility status in the upper and middle land sections. In contrast, the lower land section has a moderate fertility status. The shifting cultivation system contributes to maintaining soil organic matter content. However, to improve land productivity, phosphorus (P) and potassium (K) fertilizers should be applied, along with soil conservation techniques such as terracing or ridging to reduce erosion risk and surface runoff.